2008
DOI: 10.1080/18811248.2008.9711883
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Stainless Steels in Simulated PWR Primary Water—Effect of Chromium Content in Alloys and Dissolved Hydrogen—

Abstract: The structure and composition of surface oxide films on austenitic stainless steels in hydrogenated high-temperature water were examined by changing the chromium content in alloys and the concentration of dissolved hydrogen in high-temperature water. Auger electron spectroscopy, X-ray diffraction and analytical transmission electron microscopy revealed that the oxide films had a double-layer structure: ironbased spinels as the outer layer and chromium-rich spinel oxide as the inner layer. Increasing the chromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
24
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(34 citation statements)
references
References 23 publications
9
24
0
1
Order By: Relevance
“…The results obtained show a very low oxide layer thickness comparing to experimental data obtained under PWR conditions [9] but are in agreement with the results observed in the first PWR which operated using SS 304 as cladding material [4]. This study must be extended to evaluate the SS behavior under loss-of-coolant accident and reactivity-initiated accident.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The results obtained show a very low oxide layer thickness comparing to experimental data obtained under PWR conditions [9] but are in agreement with the results observed in the first PWR which operated using SS 304 as cladding material [4]. This study must be extended to evaluate the SS behavior under loss-of-coolant accident and reactivity-initiated accident.…”
Section: Resultssupporting
confidence: 74%
“…The chromium content plays an important role to define the composition of the oxide layer formed on the SS cladding [9].…”
Section: Corrosion Of Stainless Steel (Ss)mentioning
confidence: 99%
“…The inner oxide layer is chromium rich, protective and described as a mixed iron/chromium spinel ((Ni,Fe)Cr 2 O 4 ) while the outer oxide is found to be crystallites of geometric shapes of magnetite (Fe 3 O 4 ). Many authors observed a nickel enrichment below the metal/ oxide interface [5][6][7]. The inner oxide layer is formed by anionic diffusion whereas the outer crystallites grow from a cationic diffusion mechanism coupled with a precipitation mechanism of dissolved cations in the medium, originating from a diffusion process within the inner layer [1,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…pH control is achieved by controlling the boric acid (H 3 BO 3 ) concentration (∼500 ppm) and the lithium (LiOH) concentration (∼2.2 ppm). Corrosion experiments with simulated PWR water chemistry generally follow these guidelines [25]. In addition, minimization of dissolved oxygen to <5 ppb is desired.…”
Section: Chemistry Controlmentioning
confidence: 99%